2015
DOI: 10.3906/zoo-1406-2
|View full text |Cite
|
Sign up to set email alerts
|

First record of Russellaspis pustulans (Cockerell)(Hemiptera: Asterolecaniidae) in Turkey

Abstract: In this note, we report the presence of Russellaspis pustulans (Cockerell) (Hemiptera: Asterolecaniidae) in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The production of hydrogen peroxide causes an increase in number of phagocytes, which are responsible for breaking down different pathogens [ 28 ]. Çalişkan [ 29 ] reported that the concentration of oxalic acid is higher in leaves infected by fungus Sclerotinia sclerotiorum .…”
Section: Resultsmentioning
confidence: 99%
“…The production of hydrogen peroxide causes an increase in number of phagocytes, which are responsible for breaking down different pathogens [ 28 ]. Çalişkan [ 29 ] reported that the concentration of oxalic acid is higher in leaves infected by fungus Sclerotinia sclerotiorum .…”
Section: Resultsmentioning
confidence: 99%
“…Main symptoms of infection are formation of pits (C ßalis ßkan et al, 2015;Moursi et al, 2007;Russell, 1941), wilting of leaves and twigs, defoliation and dieback of branches, death of trees and yield loss (Abd El-Salam and Mangoud, 2001).…”
Section: Retithrips Syriacusmentioning
confidence: 99%
“…Many scale insect species are regarded as important pests in parks. Although several studies have been conducted to identify the pest species on ornamental plants in Adana (Çalışkan et al, 2015;Kaydan et al, 2013a), until now there has no specific and comprehensive study of armored scale insect species. This paper reports the survey and identification of armored scale insects in Adana, with data on their hosts and distribution.…”
Section: Introductionmentioning
confidence: 99%